Depression, quality of life, activities of daily living, and subjective memory after deep brain stimulation in Parkinson disease—A reliable change index analysis. (6th August 2019) - Pusswald, Gisela; Wiesbauer, Patrick; Pirker, Walter; Novak, Klaus; Foki, Thomas; Lehrner, Johann
Abstract : Objectives: In the field of Parkinson disease (PD) research, many studies have shown that deep brain stimulation (DBS) can soften side effects, which arise during long‐term medical therapy. This study focuses on the changes in depressive symptoms, quality of life (with the subdivisions physical and mental health), activities of daily living, and subjective memory functioning in PD patients testing the baseline and the outcome 1 year after DBS. Methods: For the first time, the reliable change index (RCI) methodology was applied to compare PD‐DBS patients (n = 22) with best medically treated PD patients (PD‐BMT; n = 28), subjects with mild cognitive impairment (MCI, n = 43) and healthy controls (n = 25) in the above‐mentioned domains. The used questionnaires included the revised Beck Depression Inventory (BDI‐II), the Short Form (36) Health Survey (SF‐36), the Bayer Activities of Daily Living Scale (B‐ADL), and the Forgetfulness Assessment Inventory (FAI). Results: The reliable change indices show high constant or improved results of the PD‐DBS patients in the domains subjective memory (85.7%‐100.0%), activities of daily living (60.0%‐90.0%), physical health summary (77.8%), depressive symptoms (61.9%), and mental health summary (50.0%) in comparison with the PD‐BMT, MCI, and control group. Conclusions: DBS is an established alternative to best medical treatment of PD. The comparisons between the PD‐DBS and PD‐BMT groups do suggest that the domains mental health, depressive symptoms, and physical health benefit most, while the domains activities of daily living and subjective memory functioning are rather constant. Nevertheless, further research is needed to identify mechanisms and predictors that lead to improvement in individual cases.